2018
DOI: 10.3233/cbm-170795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neutrophil-to-lymphocyte ratio in newly diagnosed patients receiving borte- zomib-based therapy for multiple myeloma

Abstract: Elevated NLR was associated with poor OS in MM patients receiving induction therapy with bortezomib-based regimens, but it was not an independent prognostic factor in this patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
5
8
1
Order By: Relevance
“…Recently, it has been suggested that the NLR can be used to predict prognosis in patients with MM. It has been reported in previous publications that an elevated NLR was associated with shortened OS in MM patients (4)(5)(6)23). In our study, there was no relationship between the NLR and both mortality and OS in patients with MM.…”
Section: Discussioncontrasting
confidence: 48%
“…Recently, it has been suggested that the NLR can be used to predict prognosis in patients with MM. It has been reported in previous publications that an elevated NLR was associated with shortened OS in MM patients (4)(5)(6)23). In our study, there was no relationship between the NLR and both mortality and OS in patients with MM.…”
Section: Discussioncontrasting
confidence: 48%
“…However, Zhou et al [51] reported that a high NLR (> 2.95) was associated with poor OS in MM patients treated up-front with bortezomib-based regimens, but it was not an independent prognostic factor in this cohort. These results suggest that the efficacy of NLR as a predictor of outcome may differ depending on the therapeutic agent.…”
Section: Discussionmentioning
confidence: 57%
“…In hematological malignancies, Troppan et al reported that dNLR ≥1.8 was a significant factor for 5-year disease-free survival (DFS) in DLBCL patients treated with standard rituximab and CHOP (R-CHOP) regimen 15. Elevated NLR (≥2.95) was related to inferior OS in MM patients receiving induction therapy with bortezomib-based regimens 40. Our present study demonstrated that ENKTL patients who received first-line therapy with high dNLR (≥3.6) presented lower response (CR or PR) rate when compared to patients with lower dNLR.…”
Section: Discussionmentioning
confidence: 99%